Penerapan Perawatan Luka Modern Dressing pada Lansia Penderita Diabetes Melitus - Aliyyah Amanda; Ricky Riyanto Iksan; Sri Atun Wahyuningsih (Universitas Malahayati Lampung, 2022)
ABSTRACT: APPLICATION OF MODERN DRESSING WOUND TREATMENT IN ELDERLY SUFFERERS DIABETES MELLITUS Introduction: Diabetes mellitus is a disease that is a health problem in the elderly. Diabetes mellitus is a chronic disease characterized by elevated levels of glucose in the blood. Purpose: This study aims to identify gangrene wound care with modern dressing methods in the elderly with diabetes mellitus. Method: The research method used is a case study design, which is a form of research (inquiry) or case studies and interventions about a problem that has a specific nature (particular arity). Result: The results of the research conducted on the first respondent a score of 33 on the BWAT scale did not regenerate, the second respondent experienced the healing process a score of 10, the third respondent did not regenerate with a score of 16, the fourth respondent did not regenerate with a score of 20. Conclusion: The conclusions of this study describe the Modern Dressing wound care intervention in three respondents who did not have a generation of wound healing processes and one respondent experienced the wound healing process. Keywords: Diabetes mellitus, Elderly, Modern Dressing, BWAT value ABSTRAK: PENERAPAN PERAWATAN LUKA MODERN DRESSING PADA LANISA PENDERITA DIABETES MELITUS Latar Belakang : Diabetes melitus merupakan penyakit yang menjadi masalah kesehatan pada lanjut usia. Diabetes melitus Merupakan suatu penyakit kronis yang ditandai dengan peningkatan kadar glukosa dalam darah. Tujuan: Penelitian ini bertujuan untuk teridentifikasi perawatan luka ganggren dengan metode modern dressing pada lansia dengan masalah diabetes melitus. Metode Penelitian : Metode penelitian yang digunakan case study design yaitu suatu bentuk penelitian (inquiry) atau studi kasus dan intervensi tentang suatu masalah yang memiliki sifat kekhususan (particul arity). Hasil : Hasil penelitian yang dilakukan pada responden pertama skor 33 skala BWAT tidak bergenerasi, pada responden kedua mengalami proses penyembuhan skor 10, pada responden ketiga tidak bergenerasi dengan skor 16,pada responden keempat tidak beregenerasi dengan skor 20. Kesimpulan : Simpulan dari penelitian ini menggambarkan Intervensi perawatan luka Modern Dressing pada tiga responden tidak bergenerasi proses penyembuhan luka dan satu responden mengalami proses penyembuhan luka. Kata Kunci : Diabetes melitus, Lansia, Modern Dressing, BWAT score